Membrane proteomics and transcriptomic profiling analysis of hepatic stellate cells co-incubated with Schistosoma japonicum eggs - Dong, Bowen; Zhong, Haoran; Zhu, Danlin; Li, Hao; Lu, Ke; Fu, Zhiqiang; Liu, Jinming; Jin, Yamei (Frontiers in Cellular and Infection Microbiology, 2025)
Schistosomiasis has been recognized as the second most prevalent parasitic disease worldwide, following malaria. Schistosome eggs can persist for extended periods within host hepatic tissues, leading to hepatic fibrosis primarily through the activation of hepatic stellate cells (HSCs). However, the mechanisms by which egg-secreted products modulate the activation of HSCs remain incompletely elucidated. In this study, purified Schistosoma japonicum (S. japonicum) eggs (Egg group) or corresponding unused medium (Control group) were placed in the upper chamber of a Transwell system, with HSCs cultured in the lower chamber. Following co-culture, HSCs surface proteins were eluted and subsequently analyzed by mass spectrometry. Protein identities were determined by matching spectral data against both human and schistosome protein databases. A total of 88 schistosome proteins, including both S. japonicum-specific and non-specific proteins, were identified in the Egg group. Bioinformatic analyses suggested that HSCs were exposed to egg-derived secretory proteins, indicating potential molecular interactions between schistosome eggs and host cells. Furthermore, RNA-sequencing was performed on HSCs following co-culture, resulting in the identification of 634 differentially expressed genes (DEGs), of which 454 were upregulated and 180 were downregulated. Functional enrichment analyses revealed significant involvement of these DEGs in fibrosis- and inflammation-related pathways. Collectively, this study provides novel evidence that S. japonicum eggs may remotely modulate the transcriptional profiles of HSCs via secreted bioactive molecules, thus offering a theoretical foundation for identifying potential therapeutic targets in hepatic fibrosis.